Evaluation of Virulence Factors In vitro, Resistance to Osmotic Stress and Antifungal Susceptibility of Candida tropicalis Isolated from the Coastal Environment of Northeast Brazil - Zuza-Alves, Diana L.; de Medeiros, Sayama S. T. Q.; de Souza, Luanda B. F. C.; Silva-Rocha, Walicyranison P.; Francisco, Elaine C.; de Araújo, Maria C. B.; Lima-Neto, Reginaldo G.; Neves, Rejane P.; Melo, Analy S. de Azevedo; Chaves, Guilherme M. (Frontiers in Microbiology, 2016)
Several studies have been developed regarding human health risks associated with the recreational use of beaches contaminated with domestic sewage. These wastes contain various micro-organisms, including Candida tropicalis. In this context, the objective of this study was to characterize C. tropicalis isolates from the sandy beach of Ponta Negra, Natal, Rio Grande do Norte, Brazil, regarding the expression of in vitro virulence factors, adaptation to osmotic stress and susceptibility to antifungal drugs. We analyzed 62 environmental isolates and observed a great variation among them for the various virulence factors evaluated. In general, environmental isolates were more adherent to human buccal epithelial cells (HBEC) than C. tropicalis ATCC13803 reference strain, besides the fact they were also highly biofilm producers. Most of the isolates presented wrinkled phenotypes on Spider medium (34 isolates, 54.8%). The majority of the isolates also showed higher proteinase production than control strains, but low phospholipase activity. In addition, 35 isolates (56.4%) had high hemolytic activity (hemolysis index > 0.55). With regard to C. tropicalis resistance to osmotic stress, 85.4% of the isolates were able to grow in a liquid medium containing 15% sodium chloride. The strains were highly resistant to the azoles tested (fluconazole, voriconazole and itraconazole). Fifteen strains were resistant to the three azoles tested (24.2%). Some strains were also resistant to amphotericin B (14 isolates; 22.6%), while all of them were susceptible for the echinocandins tested, except for a single strain of intermediate susceptibility to micafungin. Our results demonstrate that C. tropicalis isolated from the sand can fully express virulence attributes and showed a high persistence capacity on the coastal environment; in addition of showing high minimal inhibitory concentrations to several antifungal drugs used in current clinical practice, demonstrating that environmental isolates may have pathogenic potential.